INTEGRATING ASPECT OF STUDYING THE HISTORY OF UKRAINIAN LITERATURE IN THE PROCESS OF THE FUTURE TEACHERS OF THE UKRAINIAN LANGUAGE AND LITERATURE TRAINING - Оvdiichuk, Lilia (Mountain School of Ukrainian Carpaty, 2020)
The article emphasizes the important aspect of literary studies training of the students of speciality Ukrainian language and literature - the study of the course «History of Ukrainian Literature». The purpose of the investigation is to determine the theoretical and methodological principles of integrating study of the history of Ukrainian literature and to represent formation of integration and literary competence of future teachers of Ukrainian language and literature on this basis. The theoretical and empirical methods of scientific research were used in the process of investigation. The analytical synthetic and comparative methods were applied in the process of studying scientific sources. The empirical method was used during the process of this issue studying in real learning conditions. The content and methodological support of the integrating study of the history of Ukrainian literature was presented in the research. The dfferent types of integration are revealed: extra-subject, intra-subject, inter-artistic, which are realized at the semantic level. The interconnection with the adjacent humanities is highlighted. Intra-subject integration between the sections of literary science on fiction, biography, and creativity. The possibilities of inter-artistic integration are revealed in the process of perception and understanding of fiction with other arts. The article outlines the integration at the activity level, which occurs through the introduction of innovations into the traditional educational process of innovations: critical thinking technologies, information and communication technologies; combination of different forms of education: classroom and extracurricular; educational and research activities. The study presents the means (multimedia presentations of lectures, audio and video recordings), methods (problem, heuristic, illustration), which are applied during the integration study of the subject «History of Ukrainian Literature». It is proved that in the process of such learning the integration-literary competence is formed, which is shown through motivational-value, cognitive-reflexive, creative-activity components. comparative studies and among literary disciplines is illustrated by the example of elaboration of the writers’ biography